Understanding Student Engagement And Satisfaction With Chatgpt In Dental Education: A Qualitative Exploration - Hassan Jan; Atteeb Fatima; Mian Bilal Ahmad; Ayesha Arshad; Malik Zain Ul Abideen; Jawad tareen (Journal of Rawalpindi Medical College)
Objective: The study aimed to explore the engagement and satisfaction levels of dental students in Pakistan using ChatGPT as a supplementary learning tool.